NIVEL DE ADN-PLOIDÍA EN POBLACIONES SUDAMERICANAS Y NORTEAMERICANAS DE LA GRAMÍNEA NATIVA DISYUNTA Trichloris crinita (CHLORIDOIDEAE, POACEAE) - CARLONI, E. J. (Universidad Nacional del Litoral, 2021)
Trichloris crinita is a native grass with a naturally disjunct distribution inhabiting arid and se-mi-arid regions of South and North America. Previous studies documented a uniform ploidy level in South American populations of the species (2n = 4x = 40); however, no reference values are known for North American populations. In the present work, a protocol was implemented in the species to quantify the nuclear DNA content (DNA-ploidy indicator) by ﬂow cytometry, and this value was compared in 22 populations from South America (15) and North America (7). No differences in nuclear DNA content were found between South American and North American populations (average 2C value = 1,97 pg) neither among populations within each continent, suggesting that they all present the same ploidy level. These results provide reference values for the nuclear DNA content of T. crinita in South and North America.